2013
DOI: 10.1080/00343404.2013.837873
|View full text |Cite
|
Sign up to set email alerts
|

Houses and/or Jobs: Ownership and the Labour Market in Belgian Districts

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Recent macroeconomic work also confirms this. Using aggregate data of Belgian districts since 1970, Isebaert et al (2013) find strong empirical evidence in favour of the Oswald hypothesis.…”
Section: Introductionmentioning
confidence: 91%
“…Recent macroeconomic work also confirms this. Using aggregate data of Belgian districts since 1970, Isebaert et al (2013) find strong empirical evidence in favour of the Oswald hypothesis.…”
Section: Introductionmentioning
confidence: 91%
“…A full review of the literature on the Oswald hypothesis is beyond the scope of this paper, but it is worth noting that evidence on the Oswald hypotheses is mixed. Papers supporting the Oswald hypothesis include Pehkonen (1999), Lerbs (2011), andIsebaert et al (2015). On the other hand, Flatau et al (2003), Munch et al (2006), andValletta (2013) have results that contradict the Oswald hypothesis.…”
Section: Notementioning
confidence: 99%
“…It has been found that unemployment is higher in the regions with higher home-ownership. The most recent papers on such effects are those by Blanchflower and Oswald (2013) for the USA, Isebaert et al (2015) for Belgium, Wolf and Caruana-Galizia (2015) for Germany and Laamanen (2017) for Finland. Various studies examining the relationship between individual-level home-ownership and unemployment have found that home-owners are more successful than others in avoiding unemployment (Flatau et al , 2003; Munch et al , 2006; Van Leuvensteijn and Koning, 2004; Munch et al , 2008; Coulson and Fisher, 2009).…”
Section: Background and Literaturementioning
confidence: 99%